Clarifying MIKE and ETIS - Hunter, Nigel; Milliken, Tom (Pachyderm, 2004)
This article is a rebuttal to Reeves, et al. which was written as an opinion article in Pachyderm 35. (Reeves, et al. 2003) The authors note that it was the Conference of the Parties at CoP10 which set out the conditions regarding one-off sales of ivory and that the Standing Committee had no power to alter such decisions. They state 'The decision to develop a monitoring system to track illegal killing of elephants in the field was intitated by the African range states and agreed by CITES Parties at CoP10 in Resolution Conf.10.10'. The authors, who are both directly involved in the development and operative aspects of MIKE and ETIS, use this article to review their implementation. 'MIKE uses a statistical approach to look at relationships between the illegal killing of elephants and various possible explantory features', while 'ETIS is a comprehensive information system to track illegal trade in ivory and other elephant products. ' The authors suggest that Reeves et al., should have allowed for greater differentiation between criticism of MIKE and ETIS and that ETIS was functioning sufficiently well by CoP12 to allow for the decision for the one-off sales, but they do acknowledge that more time is needed for MIKE to be fully operational.